(untitled) (Public Sector Economics - submission site, 2021)
This article explores public value and public management through the lens of economic factors – an unusual stance since public management research mostly features the economy as background rather than foreground. Responding to calls for deeper investigations into public value, it argues that public value is not confined to the formal public sector and should also include use-values created and distributed by households, the third-sector and informal associations. Arguing that economic context is paid insufficient attention in public management research, the paper shows how alternative models are possible based on social reproduction, Regulation Theory, and Modern Monetary Theory as an alternative to traditional Keynesianism – favouring a balanced economy above balanced budget.